Fighting depopulation in Portugal: local and central government policies in times of crisis - Almeida, M. A. (Portuguese Journal of Social Science, 2018)
During one of the worst economic crisis that Portugal has faced in the last decades, with a considerable debt to deal with, emigration, population loss, ageing and unemployment afflicted our economy and society, particularly in rural territories. The aim of this article is to access the main local and central government policies to fight depopulation and territorial inequalities, and their attempts at sustainable development. What remains in the Portuguese inland regions and how is it being addressed by the few who still believe in life outside the cities? What is the role of local government in the sustainable development of the territory? All over the country, and particularly in rural areas, there is an urgent need to attract people and investment (Almeida 2017a). What are the main issues addressed by the central government to deal with this problem? For this research, a database was built with the political programmes of the 308 mayors elected in 2013, which were subject to a thorough analysis, and the new socialist government recently approved National Programme for Territorial Cohesion, aimed at promoting a more balanced territorial planning. This article describes the demographic situation and compares the municipalities’ economic strategies. The results are yet to be observed, but these new local and central policies at least reflect a change of paradigm from the social-democrat coalition government (2011–15) and introduce a discourse of hope for inland regions, even if the political time of each government (four-year terms) is never enough to solve such complex issues.